Hybrid Carbon Nanotube Fabrics with Sacrificial Nanofibers for Flexible High Performance Lithium-Ion Battery Anodes. Issue 4 (9th February 2019) - Yildiz, Ozkan; Dirican, Mahmut; Fang, Xiaomeng; Fu, Kun; Jia, Hao; Stano, Kelly; Zhang, Xiangwu; Bradford, Philip D.
Abstract : Silicon is one of the most promising anode materials for lithium-ion batteries because of its highest known theoretical charge capacity (4, 200 mAh g −1 ). However, it has found limited application in commercial batteries because of the significant volume change (up to 400%) of silicon during cycling, which results in pulverization and capacity fading. Here, we present a new method to develop a silicon - carbon nanotube (CNT) hybrid anode architecture using CNT-polymer nanofiber hybridization method. The anode material is produced by electrospinning PMMA-Si nanofibers onto aligned CNT sheets, which are drawn on a grounded, rotating take-up roller, and then subsequently decomposing the PMMA electrospun fibers at elevated temperature to create a uniform distribution of Si particles within the CNT sheets. The whole structure is then coated with pyrolytic carbon via chemical vapor deposition (CVD). The architecture provides sufficient space to accommodate the volume expansion of the Si nanoparticles. The CVD pyrolytic carbon coating helps to anchor the Si nanoparticles within CNT sheets and stabilize solid-electrolyte-interface (SEI) formation. The novel freestanding, binder free CNT-Si-C sheet hybrid exhibited improved performance in terms of excellent cycling capacity (1470 mAh g −1 ), high coulombic efficiency (98%), and good capacity retention of 88% after 150 cycles.